Implementation of Teaching Campus in EFL Classroom: A Case Study of Elementary School in East Java - Kirana, Nillah; Wulandari, Istiqomah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
The aim of this study is to describe (1) the planning of the Teaching Campus in the EFL classroom context, (2) the implementation of the Teaching Campus in the EFL classroom context, and (3) the obstacles encountered in implementing the Teaching Campus in the EFL classroom context. This study is descriptive in nature and employs a qualitative approach. Researchers collected data through observation, interviews, questionnaires, and documentation. The data analysis stage's steps, which include data reduction, data presentation, and conclusion drawing or data verification. According to the study's findings, (1) during the planning stage, teachers and students conduct online learning and students prepare activity plans based on school curriculum, and (2) during the implementation stage, students' enthusiasm for learning is very high, particularly in English subjects. Furthermore, the use of audio media can stimulate the interest of children, and (3) the difficulties encountered are related to preparing material for teaching English because there is no English subject in primary school.